PENGARUH ADVERTISING, SALES PROMOTION, DAN PUBLIC RELATIONS TERHADAP CONSUMER LOYALTY DIERA DIGITALISASI - Deswita Sari; Sugiono, Arif; Subagja, Ghia; Sari, Deswita (Business Administration Department - Universitas Katolik Parahyangan, 2023)
This study aims to determine how much influence advertising, sales promotion and public relations on consumer loyalty in purchasing products at CV. Jaya Bakery in Bandar Lampung. The independent variables used in this study are Advertising (X1), Sales Promotion (X2), Public Relations (X3) as well as Consumer Loyalty as the dependent variable. This type of research explanatory research with a quantitative paradigm. The population in this study are consumers who are followers Instagram CV. Jaya Bakery, the data was obtained from a questionnaire using a scale likert which is spread through google form to instagram social media via direct message. The sample in this study amounted to 391 respondents who were taken using the technique incidental sampling. The data in this study were analyzed using multiple linear regression analysis with the SPSS 29.0 tool. The results of this study indicate that variable advertising partially no significant effect on consumer loyalty, variable sales promotion partially significant effect on consumer loyalty, variable public relations partially significant effect on consumer loyalty. While the results are simultaneously variable advertising, sales promotion and public relations significant effect on consumer loyalty with value R Square of 52.7%.